2010 IEEE International Symposium on Electromagnetic Compatibility 2010
DOI: 10.1109/isemc.2010.5711281
|View full text |Cite
|
Sign up to set email alerts
|

Transient FDTD simulation validation

Abstract: Abstract-In computational electromagnetic simulations, most validation methods have been developed until now to be used in the frequency domain. However, the EMC analysis of the systems in the frequency domain many times is not enough to evaluate the immunity of current communication devices. Based on several studies, in this paper we propose an alternative method of validation of the transients in time domain allowing a rapid and objective quantification of the simulations results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…The GDMt indicator obtained a value of 0.43 (Good). To validate the results in time domain, the Transient Time Domain Validation (TTDV) method [11] is used, obtaining a value 0.101 for the TEA indicator.…”
Section: Methodsmentioning
confidence: 99%
“…The GDMt indicator obtained a value of 0.43 (Good). To validate the results in time domain, the Transient Time Domain Validation (TTDV) method [11] is used, obtaining a value 0.101 for the TEA indicator.…”
Section: Methodsmentioning
confidence: 99%
“…Once again, quite good correlations between the results from the method proposed and CST simulations are found. Compared to the computation tools and the methods indicated in [77][78][79][80][81][82][83][84][85][86], it is noteworthy that the computation methods established in this paper, we have benefits in terms of the simplicity and the execution time of the algorithm. Furthermore, the method presented here does not depend on the complexity of the structure under consideration.…”
Section: Validation By Full Wave Simulations With Cstmentioning
confidence: 99%
“…This efficient and rapid method of analysis is ideal for most signals. However, previous studies have identified some problems when applying the IEEE-FSV [22] to analyse particular signals [35], [37], [38]. In order to overcome these drawbacks and to make a correct validation, a variation of the IEEE-FSV method has been developed [39], [40] and is known as FSV-UPC [41].…”
Section: The Feature Selective Validation Methodsmentioning
confidence: 99%